Effectiveness Of Gray Water Mud And Cow Dung Weight Variations As Activators For Organic Waste Decomposition - Ganing, Abdul; mappau, zrimurti; Saddania, Sitti; Suaebu, Syamsuddin (Politeknik Kesehatan Kemenkes Mamuju, 2024)
Organic waste from household activities and traditional markets causes large volumes of waste to be generated every day at the Mamuju landfill. To reduce the volume of organic waste, efforts need to be made to minimize generation through innovation. This research aims to determine the effectiveness of differences between variations of gray water mud and cow dung on physical quality of compost (pH, temperature, humidity), macro elements (Nitrogen, Carbon, Phosphorus, C/N ratio , Kalium) in the decomposition of organic waste. This research involves conducting quasi experimental research on organic waste using bioactivators made from gray water sewer mud and cow dung. This research consisted of 6 (six) treatments and 1 control, so 7 (seven) composters were made. The final result of composting after analyzed for N content after 28 days are K (0,54), GW100(0,6), GW200(0,53), GW300(0,62), KS100(0,61), KS200(0,59), KS300(0,58). For P content are K(0,14), GW100(0,15), GW200(0,2), GW300(0,18), KS100(0,18), KS200(0,20), KS300(0,23). For K content are K(0,36), GW100(0,26), GW200(0,47), GW300(0,4). KS100(0,44), KS200(0,42), KS300(0,51). C/N ratio are K(70,7), GW100(58,06), GW200(87,1). GW300(56,54), KS100(60,85), KS200(58,87), KS300(60,08). And for C Organic content are K(38), GW100(35), GW200(46), GW300(35), KS100(37), KS200(35), KS300(35). The final results of composting showed that the quality of the compost with the addition bio activator of gray water mud and cow dung for 28 days is not eligible of SNI 19-7030-2004. This is due to husks have a fairly high carbon value, so 28 days is not enough to decompose into good quality compost.